Clinical experience in using lenvatinib in patients with progressive, radioactive iodine-refractory differentiated thyroid cancer - P. A. Isaev (Opuholi Golovy i Šei, 2016)
None of the variants of therapy currently available for patients with differentiated thyroid cancer (DTС) refracted to therapy with radioactive iodine 131I (RAI) is not radical and does not allow to obtain full complete recovery including this is related to traditional chemotherapy regimens increasing toxicity of treatment contribute to improvement of the clinical effect. With the introduction of multicinase inhibitors into clinical practice made it possible to increase improve therapeutic outcomes. In December of 2015 in the Russian Federation was registered lenvantinib for therapy of patients with progressing DTC resistant to RAI therapy, which according to opinion may substantially improve the results of treatment of such patients and has a potential to change current clinical practice. The article deals with description of 5 clinical cases of inoperable patients with DTС refractory to RAI therapy receiving treatment with lenvatinib in the frameworks of the international randomized clinical trial phase III SELECT. The range of therapeutic effects varied from complete regression of the tumour to stabilization.